Guide of departmental enquiries against government servants - Ramakrishna, P. V. (Hydrabad, 1982)
The warm reception accorded to the first edition of this "Guide" by all concerned necessitated the bringing of the second edition long time back. But due to the preoccupation of the author there has been some delay in fulfilling this task. Subsequent to the first edition there has been lot of case law touching the various aspects relating to departmental enquiries and some of the Conduct Rules relating to Central Government servants have also been amended. Every effort has been made to bring the rules uptodate. Important decisions of the Supreme Court and the various High Courts relating to various aspects of disciplinary matters have been added to bring the commentaries upto date.
Keywords: Civil Service Rules, Regulations, Law etc